RETROSPECTIVE ANALYSIS OF MATERNAL, NEONATAL AND EARLY-LIFE FACTORS IN CHILDREN AFFECTED WITH DIABETES MELLITUS TYPE I - Saniya, Kuan (Nazarbayev University School of Medicine, 2024)
There is a rapid growth in the incidence of Type 1 Diabetes Mellitus (T1DM) in recent years. Several types of environmental factors related to maternal, neonatal and early life may play a role as triggering factors that lead to emergence of the disease in the genetically susceptible individuals. Current evidence demonstrates conflicting results on the factors that can lead to T1DM. The main aim of this study to analyze the effect of factors, such as birthweight for gestational age, mode of delivery, type of feeding and place of residence on developing T1DM. This is case-control study of the patients that were admitted to Somatic Department of Mother and Child hospital at Astana, Kazakhstan. Patients’ guardians were asked to answer questionaries, and medical records were extracted. There were 52 patients with Type 1 Diabetes Mellitus that were listed as cases and 50 patients that were included as controls. Descriptive data include date of birth, sex, place of residence, birthweight, height at birth, week of birth, type of feeding, birth type, allergies, family history and parity. The association between risk factors and T1DM was assessed by logistic regression analysis by calculation of the odds ratios(ORs) and 95% confidence intervals (CIs). In the multivariate analysis length at birth revealed a significant association with T1DM risk in children born taller (Adjusted OR 1.30, p-value 0.036). Weight, gender, birth timing, residency, feeding methods, and delivery mode resulted in no significant association with T1DM risk.
Keywords: type of access: gated access